The Responses of the Ribonuclease A Superfamily to Urinary Tract Infection - Becknell, Brian; Ching, Christina; Spencer, John David (Frontiers in Immunology, 2019)
The lower urinary tract is constantly exposed to microorganisms that inhabit the gastrointestinal tract, yet the urinary tract resists infections by gut microorganisms. This resistance to infection is mainly ascribed to the versatility of innate immune defenses of the bladder urothelium, the kidney epithelium, and resident or circulating immune cells. In recent years, surmounting evidence suggests that these cell types produce and secrete soluble host defense peptides, including members of the Ribonuclease (RNase) A Superfamily, to combat invasive bacterial infection. While some of these peptides, including RNase 4 and RNase 7, are abundantly produced by epithelial cells, the expression of others, like RNase 3 and RNase 6, increase at infection sites with immune cell recruitment. The objective of this mini review is to highlight recent evidence showing the biological importance and responses of RNase A Superfamily members to infection in the kidney and urinary tract.